2018
DOI: 10.1111/liv.13926
|View full text |Cite
|
Sign up to set email alerts
|

Territory‐wide population‐based study of chronic hepatitis C infection and implications for hepatitis elimination in Hong Kong

Abstract: Our diagnosis rate, treatment rate and mortality rate reduction were still low, particularly the Peg-IFN outcomes, making it difficult to meet the WHO hepatitis elimination targets. A more generalized use of DAAs is urgently needed to improve the situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…All 16 patients were chronically infected with HCV and had been followed up for a median duration (interquartile range) of 6 (2.75–9.25) years. Half the patients were infected with genotype 1 HCV, and 5/16 (31.25%) patients were infected with genotype 6, which is the second most common HCV genotype in Hong Kong [16]. HBsAg positivity was documented in 4/16 (25%) cases, whereas 1 patient was known to be co-infected with HIV.…”
Section: Resultsmentioning
confidence: 99%
“…All 16 patients were chronically infected with HCV and had been followed up for a median duration (interquartile range) of 6 (2.75–9.25) years. Half the patients were infected with genotype 1 HCV, and 5/16 (31.25%) patients were infected with genotype 6, which is the second most common HCV genotype in Hong Kong [16]. HBsAg positivity was documented in 4/16 (25%) cases, whereas 1 patient was known to be co-infected with HIV.…”
Section: Resultsmentioning
confidence: 99%
“…In Hong Kong, 40-50% of injection drug users are chronically infected with hepatitis C virus [3,26]. Although the diagnosis rate is 50% in the overall community [27], the diagnosis rate among injection drug users is much lower, and only a quarter of patients diagnosed to have CHC would eventually receive antiviral therapy. It is also noteworthy that the proportion of patients with other psychiatric illnesses who had CHC (0.9-3.3%) was still much higher than the population prevalence of positive anti-hepatitis C virus Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased public and private funding is essential to support care and treatment services . In a territory‐wide population‐based study from Hong Kong the authors concluded that the reduction in the diagnostic, treatment and mortality rates was low, especially since treatment with peg‐IFN was still used in some cases making make it difficult to reach the WHO hepatitis elimination target . The authors concluded that generalized use of new DAAs was also urgently needed in this region.…”
Section: Mathematical Modellingmentioning
confidence: 99%